A cross sectional study of prevalence and association of sensorineural hearing loss in patients with type 2 diabetes mellitus - M. K., Vybhavi; V., Srinivas; Muddaiah, Dechu (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Background: Diabetes mellitus (DM) is a chronic metabolic disorder associated with various long-term complications and among them hearing loss is one of the underestimated comorbidity. Objectives were to evaluate the prevalence of sensorineural hearing loss (SNHL) and to determine the association of age, gender, duration and control of DM with hearing loss. Methods: A total of 130 patients aged 30-65 years with type 2 DM were included in this cross-sectional study. All patients were subjected to detailed history taking, ear, nose and throat examination followed by pure tone audiometry and measurement of glycosylated haemoglobin (HbA1c) levels. Results: In this study, SNHL was seen in 70.76% of patients. Statistically significant association was found between the older age group, longer duration of DM and SNHL (p=0.00 and 0.002). Significant association was also seen between the severity of hearing loss and HbA1c levels with p=0.01. Conclusions: Our study showed a high prevalence (70.76%) of SNHL among type 2 diabetic patients and evidently demonstrated significant association between age of the patients, duration of diabetes and SNHL as well as the association between glycemic control and the severity of hearing loss.